The solar chromospheric Ca and Mg indices from Aura OMI. Issue 8 (30th April 2013) - DeLand, Matthew; Marchenko, Sergey
Abstract : [1] Direct observations of long‐term variations in solar UV irradiance from satellites, although important for monitoring the energetic forcing of the Earth's atmosphere, is challenging because of the difficulty of accurately tracking instrument response changes. Proxy indexes based on core‐to‐wing ratios of solar Fraunhofer lines, such as the Mg II feature at 280 nm, can minimize the impact of both time‐ and wavelength‐dependent instrument changes to better monitor solar UV activity. Here we present new data sets from the Ozone Monitoring Instrument (OMI) on the Aura satellite, which began operations in late 2004. The high quality of OMI irradiance measurements allows us to construct daily indexes for the Mg II, Ca II K (393.4 nm), Ca II H (396.8 nm), and Mg I (285.2 nm) lines. The OMI Ca II K index is well correlated with the Mg II index measured by multiple instruments, as well as the ground‐based National Solar Observatory (NSO) Ca II K 1.0 Å index data derived from Integrated Sunlight Spectrometer measurements. OMI Ca II K data can be used to evaluate anomalous short‐term features in the NSO data set. The OMI solar data products represent a valuable addition to current data sets. Key Points: Ca II K and Mg II indices can be produced from OMI solar measurements. OMI Ca II K index and Mg II index agree well with other data sets. OMI Ca II K index can validate ground‐based NSO Ca II K index data.